18-step back-to-back voltage source converter with pulse interleaving circuit for HVDC application. - Hye-Yeon Lee (Journal of electrical engineering & technology)
This paper proposes an 18-step back-to-back (BTB) voltage source converter using four sets of 3-Level converter modules with auxiliary circuits to increase th number of steps. The proposed BTB voltage source converter has the independent control capability of active power and reactive power at the interconnected ac system. The operational feasbility of the proposed BTB converter was verified through many simulations with PSCAD/EMTDC software. The feasbility of hardware implementation was verified through experimental results with a scaled hardware protype. The proposed BTB converter could be widely applied for interconnecting the renewable energy source to the power grid.